10-7h-5h=-10-10h

Simple and best practice solution for 10-7h-5h=-10-10h equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 10-7h-5h=-10-10h equation:


Simplifying
10 + -7h + -5h = -10 + -10h

Combine like terms: -7h + -5h = -12h
10 + -12h = -10 + -10h

Solving
10 + -12h = -10 + -10h

Solving for variable 'h'.

Move all terms containing h to the left, all other terms to the right.

Add '10h' to each side of the equation.
10 + -12h + 10h = -10 + -10h + 10h

Combine like terms: -12h + 10h = -2h
10 + -2h = -10 + -10h + 10h

Combine like terms: -10h + 10h = 0
10 + -2h = -10 + 0
10 + -2h = -10

Add '-10' to each side of the equation.
10 + -10 + -2h = -10 + -10

Combine like terms: 10 + -10 = 0
0 + -2h = -10 + -10
-2h = -10 + -10

Combine like terms: -10 + -10 = -20
-2h = -20

Divide each side by '-2'.
h = 10

Simplifying
h = 10

See similar equations:

| -22-(-35)= | | 2(3x-y)=14 | | 14-8x=-3x-8 | | -5w-7=-37 | | 75-(-25)= | | 4r=-3+7r | | -70-5= | | -80-(-40)= | | X=320000 | | X=320000 | | (8x^4)(2x^3)= | | t=10+5 | | 17=c+10 | | x+y=320000 | | 5b+6-6b+r=19 | | 3j-8=5j+4 | | 5.4=3s | | x-69=-6x+99 | | -9=-6+3(5-m) | | 7(7x+5)=7(x-1) | | 5x-111=-7x+105 | | x=180-88 | | x+3.5=10.2 | | 2=3x-10 | | 4=14-k | | -2s-14s-5=11 | | -3t+7=-8t-3 | | 2d+d-3=6 | | p-7=-5 | | -4x+9(x-3)=10x+2 | | 20=8(v-90)-52 | | 3n+6=-10n-7 |

Equations solver categories